MERCURY ACCUMULATION IN GOLD MINE TAILING BY SWEET SORGHUM INOCULATED WITH CHROMIUM UPTAKE ENHANCING RHIZOBACTERIA - Utami, Desi; Takahi, Sachiko; Dwidya Prijambada, Irfan (International Journal of Biosciences and Biotechnology; Vol 1 No 2 (2013), 2013)
Small scale gold mining provides an important source of income for miners in rural communities whereeconomic alternatives are extremely limited. However, it releases mercury which damages the environmentand poses risks to those in the nearby community. Phytoremediation is considered as a simple and costeffective method for the cleanup of heavy metal from contaminated soil. Phytoremediation is a technologythat uses plants to degrade, extract, contain, or immobilize contaminants from soil and water. In particular,phytoextraction is the uptake of contaminants by plant roots and translocation within the plants to shootsor leaves. Contaminants are then removed by harvesting the plants. The objective of this research is toexamine the ability of sweet sorghum and its inoculation using chromium uptake enhancing rhizobacteriafor phytoremediation of gold mine tailing. Two varieties of sweet sorghum were used in this experiment, i.e.FS501, and KCS105. The seed of the sweet sorghum was sown in mercury containing tailing or a mixture ofit with uncontaminated soil. Plant biomass and its mercury content were determined 35 days after sowing.Only FS501 was able to grow on tailing containing 26.94ppm of mercury. Inoculation of the sweet sorghumwith the rhizobacteria does not aff ect its biomass but increase its mercury uptake signifi cantly. Mixing thetailing material with uncontaminated soil causes an increase in biomass but reduce the mercury content inplant signifi cantly. As a result, the amounts of removable mercury decrease signifi cantly. Inoculation withthe rhizobacteria has no eff ect on mixed material
Keywords: Sweet sorghum, mercury, uptake enhancing, rhizobacteria